Effect of anaemia on maternal and fetal outcome: an observational study - Dwivedi, Seema; Gupta, Garima; Singh, Ritu; Malik, Anchal; Sharma, Karishma (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anaemia in pregnancy is a globally health-related issue that affects both mothers and their new-born. Hence an observational study to see the effect of anaemia on maternal and foetal outcome was conducted. Methods: 15024 mothers coming in OPD or IPD in past 4 years were recruited and their haemoglobin measured. Descriptive statistics was used for baseline characteristics. This observational study was conducted in department of obs and gynae, GSVM Medical College Kanpur from August 2018 to August 2022. All the data gathered was processed by SPSS version 25. Results: The main outcomes included 4 maternal outcomes (postpartum haemorrhage, shock, ICU admission, and maternal mortality) and 4 neonatal outcomes (foetal growth restriction, birth weight, NICU admission, stillbirth). 60.03% of the mothers were anaemic in our study. Maternal and foetal complications were more in anaemic than non-anaemic mothers with incidence of PPH, shock, ICU admission, and maternal mortality being 14.07%, 11.33% ,4.30 and 1.31% respectively than non-anaemic mothers with incidence of 11.22%, 7.26%, 1.76%, and 7.28% respectively. Foetal outcome was also poorer in anaemic mothers with incidence of FGR, LBW, NICU admission, Still birth being 3.15%, 8.85%, 12.96%, and 1.09% higher than non-anaemic group with incidence being 1.80%, 3.43%, 9.75%, and 0.30 % respectively. Conclusions: This observational study provides valuable insights into the effect of anaemia on both maternal and foetal outcomes. It emphasizes the importance of early detection and management of anaemia to mitigate the risks associated with this condition.